Motor Clumsiness in 9-12 Year-Old Greek Schoolchildren - Ellinoudis Θεόδωρος; Kourtessis Θωμάς; Kiparissis Μιχαήλ; Papalexopoulou Νικολίτσα (Inquiries in Physical Education and Sport, 2008)
The purpose of the present study was to determine the incidence of motor clumsiness among Greek schoolchildren. Participants were 220 boys (n = 110) and girls (n =110), aged 9-12 years, all elementary-school students from the areas of Macedonia, Thrace and Peloponissos. Movement Assessment Battery for Children (Henderson & Sugden, 1992), was used for the identification of movement difficulties. The battery assesses three motor domains: manual dexterity, ball skills and balance (static and dynamic). The process revealed that 10% of the participants (22 children, 11 boys and 11 girls) exhibited definite coordination difficulties, while another 14.1% (31 children, 18 boys and 13 girls) exhibited moderate and mild difficulties. The above results are in accordance with the results of the relative international bibliography. However, the present results did not support previous findings that stressed the fact that more boys than girls face movement difficulties. Furthermore, statistical analysis revealed that “sex” did not have a significant effect on the assessment process. Conclusively, it seems that a significant number of children face motor clumsiness within the Greek school environment. Identification and assessment protocols should be an integral part of the education process, in order to provide proper educational and academic support.